Boron additive passivated carbonate electrolytes for stable cycling of 5 V lithium–metal batteries. Issue 2 (13th December 2018) - Yue, Hongyun; Yang, Yange; Xiao, Yan; Dong, Zhiyuan; Cheng, Shuguo; Yin, Yanhong; Ling, Chen; Yang, Weiguang; Yu, Yanhao; Yang, Shuting
Abstract : The limitation of a high-voltage lithium (Li) metal battery lies in the absence of a robust electrolyte that can endure oxidation loss at a high-voltage cathode and suppress the dendrite growth at a Li metal anode. Abstract : The limitation of a high-voltage lithium (Li) metal battery lies in the absence of a robust electrolyte that can endure oxidation loss at a high-voltage cathode and suppress the dendrite growth at a Li metal anode. The challenge becomes especially serious when the cathode voltage reaches 5 V and above. Here, we developed an additive-containing electrolyte that can concurrently stabilize the Li metal anode and the 5 V class LiNi0.5 Mn1.5 O4 (LNMO) cathode by introducing tris(pentafluorophenyl)borane (TPFPB) to the traditional ethylene carbonate/ethyl methyl carbonate (EC/EMC) electrolyte. The boron element and pentafluorobenzene in TPFPB induce preferential formation of a steady and smooth interfacial layer on both the Li and LNMO electrodes, subsequently preventing the decomposition of the electrolyte, impeding the pulverization of the cathode electrode, and retarding the growth of Li dendrites. Accordingly, we accomplish high average coulombic efficiency of >99.2% and superior capacity retention of 90% after 500 cycles at 0.5C with charge cut-off voltage of 4.95 V, which is one of the highest results for cycling among 5 V-class Li metal batteries with 90% capacity retention. This study provides essential technological implications for the electrolyte design for high-voltage Li–metal batteries.